Interlayer engineering of lattice dynamics and elastic constants of 2D layered nanomaterials under pressure - Guoshuai Du; Lili Zhao; Shuchang Li; Jing Huang; Susu Fang; Wuxiao Han; Jiayin Li; Yubing Du; Jiaxin Ming; Tiansong Zhang; Jun Zhang; Jun Kang; et al. (Nature Communications)
Abstract Interlayer coupling in two-dimensional (2D) layered nanomaterials can provide us strategies to evoke their superior properties, such as the layer-dependent phonon vibration, the formation of moiré excitons and related nontrivial topology. However, to accurately quantify interlayer potential and further measure elastic properties of 2D materials remain challenging, despite significant efforts. Herein, the layer-dependent lattice dynamics and elastic constants of 2D nanomaterials have been systematically investigated via pressure-engineering strategy based on ultralow frequency Raman spectroscopy. The shear and layer-breathing modes Raman shifts of 2H-MoS2 with various thicknesses are analyzed by the monoatomic chain model (MCM). Intriguingly, it is found that the layer-dependent dω/dP of shear (S N,1) and breathing (LB N,N-1) modes display the opposite trends, quantitatively consistent with MCM analysis, our molecular dynamics simulations and density functional theory calculations. The diatomic chain model is combined with Raman data to analyze the intralayer and interlayer shear force constants and their pressure coefficients, revealing a strong dependence on the number of layers. These results can be generalized to other van der Waals systems, and may shed light on the potential applications of 2D materials in nanomechanics and nanoelectronics.